Analysis of Innovation of The Online Education System During the Pandemic - Labale, Dzulfikar; Puspitasari, Dina (Institut Agama Islam Negeri Sorong, 2022)
The current learning process must still be carried out by all students even though they are in a pandemic outbreak situation. Education is the main key in preparing superior human resources to be able to compete at the global level. The COVID-19 pandemic has changed the entire educational setting from being face-to-face in the classroom to a learning process with a learning from home system. Learning during the current pandemic requires innovation in the education system to formulate the right learning models and methods so that the process of teaching and learning activities can take place effectively. This study aims to examine the analysis of education system innovations during a pandemic. The research method uses the literature review method with data sources obtained from related documents and articles. The results showed that the innovation of online or online learning systems has a great influence on the current education system, even though it is in a pandemic situation, but this innovation provides benefits and satisfactory results for students and educators.